KEY RESPONSIBILITIES IN THE PROCESS OF PUPILS' INDEPENDENT WORK IN THE SUBJECT OF TECHNOLOGY - SOLTES, Jaroslav (Journal of Technology and Information Education, 2016)
The aim of the presented study is to present one of the essential competences of pupil, and that is the creation of selected key competencies. Selected competencies in the subject Technology comprises of capabilities of pupil that enable them to clarify the natural laws, use and operate modern technical resources, and to master technical knowledge. The basis for successful teaching is to create conditions for the development of competencies and possible application of different kinds of independent and creative activities in the classroom. In the realization of research in our workplace, we have investigated those competencies, which carry distinctive features of activities that achieve very good performances of pupils in the technical field.
Keywords: pupil; key competencies; research on selected key competencies; interactive teaching